Humanitarian intervention in the long nineteenth century : Setting the precedent - Heraclides, Alexis; Dialla, Ada; Project Muse. (Manchester : Manchester University Press, 2015)
This book is a comprehensive presentation of humanitarian intervention in theory and practice during the course of the nineteenth century. Through four case studies, it sheds new light on the international law debate and the political theory on intervention, linking them to ongoing issues, and paying particular attention to the lesser known Russian dimension. The book begins by tracing the genealogy of the idea of humanitarian intervention to the Renaissance, evaluating the Eurocentric gaze of the civilisation-barbarity dichotomy, and elucidates the international legal arguments of both advocates and opponents of intervention, as well as the views of major political theorists. It then goes on to examine four cases as humanitarian interventions: the Greek War of Independence (1821-31), the Lebanon and Syria (1860-61), the Bulgarian atrocities (1876-78), and the U.S. intervention in Cuba (1895-98).
Humanitarian intervention today -- Theory. Introduction ; The origins of the idea of humanitarian intervention : just war and against tyranny ; Eurocentrism, 'civilization' and the 'barbarians' ; International law and humanitarian intervention ; Intervention and non-intervention in international political theory -- Practice. Introduction ; Intervention in the Greek War of Independence, 1821-32 ; Intervention in Lebanon and Syria, 1860-61 ; The Bulgarian atrocities : a bird's eye view of intervention with emphasis on Britain, 1875-78 ; The Balkan crisis of 1875-78 and Russia : between humanitarianism and pragmatism ; The US and Cuba, 1895-98 -- Conclusion. Assessment.
In English.
Description based on print version record.
Keywords: Law, Politics & Government; International Relations; Humanitarian intervention; POLITICAL SCIENCE -- American Government -- General; LAW -- International; POLITICAL SCIENCE / American Government / General; LAW -- International; International relations; Politics and government; Society and social sciences Society and social sciences; Droit d'ingerence humanitaire -- Études de cas; Droit d'ingerence humanitaire -- Histoire -- 19e siecle; Humanitarian intervention -- Case studies; Humanitarian intervention -- History -- 19th century; History; Case studies; Electronic books